IMPLIKATUR DALAM CERAMAH â€œREKONSILIASI PERAN PEMUDA DALAM BIDANG KEBANGSAANâ€ (TINJAUAN PRAGMATIK) - Anjarsari, Marianita (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This study aims to describe the forms of implicature containing preaching messages in the lecture "Reconciliation of Youth Roles in the Frame of Nationality". This research is a descriptive qualitative research. The data source in this study is the video lecture "Reconciliation of Youth Roles in the National Frame" conducted by K.H. Ahmad Muwafiq on October 10, 2019 at the Karangdurin Islamic Boarding School, Tlambah, Sampang, Madura, East Java. The data in this study are speech lectures conducted by K.H. Ahmad Muwafiq and the listeners. Data collection techniques used in this study were the SBLC technique (see free folding) and note technique. The results of this study indicate that in the lecture "Reconciliation of Youth Roles in the Frame of Nationality" four forms of implicature were held which contained the message of da'wah. The form of the impilator is 1) the implicature in the form of a faith message, 2) the implication in the form of sharia or worship, 2) the implication in the form of a moral message, and 4) the imature in the form of a national message.